Integration of Artificial Intelligence in Islamic Higher Education: Comparative Responses between Indonesia and Thailand - Fatah Syukur; Ahmad Maghfurin; Uswatun Marhamah; Phaosan Jehwae (Universitas Pesantren Kh abdul Chalim Mojokerto, 2024)
This study aims to compare the responses of Islamic Universities in Indonesia and Thailand to the adoption of artificial intelligence (AI) in Islamic education learning. This comparative qualitative research collected data from in-depth interviews, participatory observation, and analysis of relevant documents at UIN Walisongo Semarang (Indonesia) and Darul Maarif Islamic College Patani (Thailand). The collected data were analyzed thematically using triangulation, member checking, and audit trail validation models. The findings of this study show similarities and differences; both institutions have not specifically incorporated AI into the formal curriculum as a course, only integrating it implicitly in the hidden curriculum such as research, workshops, and seminars. Indonesian Islamic universities view AI as an important tool for modernizing Islamic education, especially in distance learning and the digitalization of Qur'anic teaching. In contrast, although AI is not explicitly banned in Thailand, there are concerns about its impact on the role of traditional teachers and Islamic cultural values. Regarding ethics, Indonesian students are less likely to consider the potential bias of AI towards Islamic religious information. In contrast, Thai students are more wary of the impact of technology on their religious values. Mastery of AI technology also showed significant differences, with Indonesian students being more advanced.